THEORETIC APPROACHES TO MULTILINGUAL EDUCATIONAL PROGRAM DESIGN IN LUXEMBOURG - Holovatenko, Tetiana (Educological discourse, 2018)
The paper reviews theoretical approaches to multilingual educational program design on an example of University of Luxembourg. This article dwells on the concept of multilingualism. As a result of analyzing different approaches to defining multilingualism, we refer it as ability of a person to communicate in more than one language orally or in writing. One of multilingual countries across European Union is Luxembourg, with Luxembourgish, German and French as official languages. The peculiarities of the Luxembourgish educational system, making its experience important to us, are the following: teaching official languages in consecutive order within schooling and teacher preparation to working in multilingual environment. To provide the highest quality of preparation, future teachers study within multilingual educational programs. In this paper we analyze 4 models of multilingual education according to David Nunan and Agnes Lam. According to researchers, Models of Language Shift (Type A) are represented by submersion programs, intensive programs and cultural sensitivity programs. These programs are implemented as additional for immigrant children, not speaking the language of schooling. Models of Language Shift (Type B) are represented by transitional bilingual programs and bridging programs aiming at preparing students to studying through a dominant language during the next level of education. Models of Language Maintenance (Type A) involve learning foreign languages, not widely spoken in the area. Models of Language Maintenance (Type B) comprise learning a language, crucial for communicating in the community through CLIL. The research showed only Models of Language Maintenance are used in University of Luxembourg. The article also focuses on principles of multilingual educational program design. Considering current situation at Ukrainian higher school, possibilities to implement multilingual educational programs into preparing future teachers are analyzed.